ChemInform Abstract: Trihaloisocyanuric Acid/Triphenylphosphine: An Efficient System for Regioselective Conversion of Epoxides into Vicinal Halohydrins and Vicinal Dihalides under Mild Conditions. Issue 38 (September 2016) - de Andrade, Vitor S. C.; de Mattos, Marcio C. S.
Abstract: Tribromoisocyanuric acid gives the corresponding bromo compounds in similar yields.